Computation Analysis of Regularization Methods and Parameter Selection for Acoustic Source Radiation Modes Reconstruction of Vibrating Plates - Roman-Asenjo, P; Corral-Rodriguez, L (The Institute of Noise Control Engineering of the USA, Inc., 2021)
Source localization and power estimation is a topic of great interest in acoustics and vibration. Acoustic source radiation modes reconstruction is a method of particular interest. Solutions lead to determine sound/vibration power and surface velocity distribution from sparse acoustics samples. It has been shown that the quality of the results depends on Tikhonov regularization parameter. This inverse method is based on the radiation resistance matrix and we show that a SIMT computing approach for GPU devices exhibit better speed performance than common approaches to achieve the solution. We compare four regularization and three estimating methods for regularization parameters. We use a similarity measure for the simulated cases in three frequencies. Tikhonov regularization exhibits best reconstruction results. However, truncated singular vector decomposition also shows good performance with the advantage of not using a regularization parameter. GPU implementation reduces reconstruction computing time by at least a half. © INTER-NOISE 2021 .All right reserved.